Relationship Between Perceived Stress and Psychological Distress Facing Nursing Students in College of Nursing Gombe, Nigeria - Musa, Abubakar; Saba, Y. Aisha (Kashere Journal of Education, 2022)
The paper is to examine relationship between perceived stress, and psychological distress facing nursing students in College of Nursing, Gombe state. The research design was correlation design. A Research question and one Null hypothesis was formulated to guide the study. The population was all nursing students of the College of nursing Gombe. The entire students were used without any sampling; this is because the students were not too large to be managed. ‘perceived stress scale, and ‘Kessler Psychological Distress Scale’ were adapted and used as Instruments for data collection. Two experts from the department of Educational Foundation Abubakar Tafawa Balewa University, Bauchi validated the two instruments. The internal consistency of the instruments showed Cronbach’s alpha of 0.75 for Emotional Intelligence scale, and 0.64 for Psychological Distress scale respectively. Two hundred and twenty-five (225) nursing students participated in the study. Male = 34 and female =191 (n=225). Ethics approval was obtained from the College Management. Research Question was analyzed using mean and standard deviation, Pearson’s Correlation, was used to address the Hypothesis. The findings of the study revealed that, most of the participants had high level of perceived stress, and were experiencing high degree of psychological distress. Positive correlation was found between perceived stress, and Psychological Distress; it was concluded that the higher the level of perceived stress, the higher experiencing psychological distress among Nursing students. Therefore, it is recommended that further exploration to better understanding of the interrelationships of perceived stress, Psychological distress and coping strategies to help develop students’ perceived stress and coping strategies is needed. Inclusion of strategies to enhance perceived stress management in the nursing curriculum which may be beneficial to Nursing Students as this can help to improve their academic and clinical performance.